Pengaruh Online Customer Rating dan Varian Menu terhadap Loyalitas Konsumen pada Aplikasi GoFood dengan Moderasi Price Discount - Febriantika, Inda; Saptaria, Lina (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The purpose of this study was to analyze the influence of online customer ratings and menu variations on consumer loyalty to the GoFood application, with price discounts as a moderating variable. Quantitative data were collected through an online questionnaire from 92 GoFood application users who were students at the Islamic University of Kadiri. The data were analyzed using the PLS-SEM method. The results showed that online customer ratings and menu variations had a positive and significant effect on consumer loyalty among GoFood application users. Furthermore, price discounts were not able to strengthen the relationship between customer ratings and consumer loyalty, but were able to positively moderate the relationship between menu variations and consumer loyalty. The implications of this study contribute to culinary entrepreneurs and management of food delivery service platforms such as GoFood in developing digital marketing strategies that can increase consumer loyalty.